A comprehensive association analysis between homocysteine metabolic pathway gene methylation and ischemic stroke in a Chinese hypertensive population. Issue 3 (31st December 2020) - Li, Bo; Li, Yuying; Xu, Shan; Chen, Hongen; Dai, Shudong; Peng, Xiaoling; Wang, Li; Liang, Yaping; Li, Cheng; Tang, Biwei; Zhu, Liqing; Zhang, Tao; et al.
Abstract: Background: Ischemic stroke (IS) is a serious global health burden. In order to improve our understanding of the risk factors associated with IS, we investigated the combined effect of the methylation of five genes related to the metabolism of homocysteine on developing IS. Methods: Quantitative methylation‐specific PCR was used to measure the levels of promoter methylation in hypertensive and stroke patients. The cutoff value calculated by the maximum Youden index was used to classify the levels of gene methylation as hypomethylation and hypermethylation. Logistic regression was used to explore the relationship between gene methylation and IS. Results: The methylation levels of the genes encoding methylenetetrahydrofolate dehydrogenase 1 [ MTHFD1 ], cystathionine β‐synthase [ CBS ], and dihydrofolate reductase [ DHFR ] in hypertensive patients were higher than those in stroke patients (all p  < 0.01). MTHFD1 hypermethylation, CBS hypermethylation, and DHFR hypermethylation were protective factors for stroke after adjustment for confounding factors. Compared with individuals carrying none of the biomarkers, the ORs [95% CIs] for stroke of those with 1 and 2 elevated biomarkers were 4.068 [1.670–9.913] and 15.345 [6.198–37.994] after adjustment for confounding factors. The participants with a larger number of biomarkers had an increased risk of stroke ( p for trend <0.001). For the combination biomarkers, the area under the curve of the receiver operating characteristic was 0.716. Conclusion: A significant linear relationship between the number of elevated biomarkers and the risk of stroke has been observed, suggesting that elevations of these biomarkers could be used for potentially predicting the disease. Abstract : A significant linear relationship between the number of elevated biomarkers and the risk of stroke.